Bioactive flavonoids of the flowers of Butea monosperma - Ratchanaporn Chokchaisiri (2018)
One new dihydrochalcone, dihydromonospermoside (7), was isolated from the flowers of Butea monosperma together with three known chalcones, butein (2), monospermoside (4) and isoliquiritigenin (8), one flavone, 7,3',4'- trihydroxyflavone (6), four flavanones, (-)-butin (1a), (-)-butrin (3a), (+)-isomonospermoside (5b) and (-)-liquiritigenin (9a), and three isoflavones, formononetin (10), afrormosin (11) and formononetin-7-O-β-D-glu- copyranoside (12). The structure of the new compound was elucidated by spectroscopic techniques whereas those of the known compounds were identified by comparisons of spectroscopic and some physical data with those of reported compounds. The absolute configurations at the 2-position of the flavanones 1a, 3a, 5b and 9a were established to be 2S, 2S, 2R and 2S, respectively, by circular dichroism spectral measurements and were confirmed by comparison of the optical rotations with those of reported values and by enzymic hydrolysis of the glucosides to the corresponding aglycones. The isolated flavonoids exhibited varying antimycobacterial activity with the chalcone 2 being the most active compound (MIC 12.5 μg/ml). © 2009 Pharmaceutical Society of Japan.